Pengembangan Metode Pembelajaran Pendidikan Agama Islam Bagi Guru Di Dusun Juruh Kec. Kelapa Kab. Bangka Barat - Hawari, Muhammad Rifqi; Pasaribu, Munawir (Yayasan Rahmat Islamiyah, 2024)
This research is a form of learning model which contains learning approaches, learning methods, learning strategies and learning techniques and tactics. These forms are methods or strategies that can be used by a teacher to provide understanding to their students. The aim of this research is not to find out about the development of learning methods in Islamic religious education. The research method used by the author is qualitative research, using a library research approach. The results of this research show that in the Dusun Juruh school, West Bangka sub-district, there is a lack of learning methods applied by the teachers at the school, so this research aims to increase the development of learning using demonstration methods and lecture methods because students in these schools quickly catch on with these methods. a teacher must be intelligent in understanding and able to provide understanding to students, because students' models of understanding are different, as well as various learning methods, the teacher must adapt to the patterns and limits of students' abilities in absorbing lessons. Perfect student understanding is a common hope, but this understanding goes back to the teaching method adopted by a teaching staff, so from the writing above it explains the methods and strategies in learning, the models above can be a reference in providing learning material to children educate.Â